TRIPLE TEST CROSS ANALYSIS AND SIX POPULATIONS WERE USED TO DETERMINE GENETIC VARIABILITY AND DIVERSITY FOR YIELD AND ITS COMPONENTS IN BREAD WHEAT (Journal of Pharmaceutical Negative Results, 2023)
Joint scaling test x2 and non-allelic interaction scaling test (A, B, and C) and a six-parameter model was used to assess the effectiveness of the genetic model and calculates the genetic elements for days to heading, flag leaf area, (number of spikes / plant, number  of grains/spike , 1000 - grain weight and grain yield/ plant (g) using  six populations  (P1, P2,  F1, F2, BC1 and BC2)  and triple test crosses analysis of two  wheat  crosses;  1.  Gemmeiza11 X Misr1 and 2. Gemmeiza 12 X Misr2. A randomized complete block design with three replications   was used.  The  obtained  results  indicated  the importance  of additive  genetic  variance (D) in the genetic  control  of days to heading  and flag leaf area  for  Gimmeiza   12 X  Misr2 in tow methods analysis  and  number  of  spikes / plant  in  two  crosses in tow method analysis. Heritability in narrow   sense was more than 0.50.  While the dominant type controlling for the remaining traits in two crosses was determined to be the dominance genetic variance (H),   the  value  of  (H/D)05  was  more  than  one  for  these characters   and  heritability   in  narrow  sense  was  less  than  0.50.  Joint scaling test (X2) and non-allelic interaction (A, B, and C) demonstrated that a basic genetic model was sufficient to explain the inheritance of number of spikes/plant for Gemmeiza 12 X Misr1, epistasis played a great role of controlling remaining characters  in two crosses.  Additive (d) and additive X dominance  (j) were significant for days to heading  and number  of grains /spike  (1st  and  2nd  crosses),  1000  grain weight and grain yield / plant for 2nd cross. The digenic  interaction  type dominance  X dominance   (l) controlling   days  to   heading   (1st and 2nd crosses),   Number of spikes per plant (1st cross), number of grains per spike, weight in 1000 grains, and yield in grains per plant (2nd cross).  The main limiting variables for selecting the best breeding technique are thought to be an understanding of the type of gene action controlling mechanism of the yield and yield components paired with the reproduction system.  These information  are  of  great  interest  for  plant  breeder  to  release  high  yielding  wheat cultivars as well as early mature ones.